Study on conformational structure of tamarind seed polysaccharide and its sulfated derivative by light scattering method - Tan, Bui Ngo; Minh Thu, Quach Thi; Thu Thuy, Thanh Thi (Vietnam Journal of Chemistry, 2017)
The aim of this study was to study the conformational changing when sulfated groups were introduced to the molecular chain of native tamarind seed polysaccharide (TSP). Light Scattering (LS) method was used to determine conformation of TSP and its sulfated derivative TSPS. The results indicated that both TSP and TSPS have a highly branched and more sphere-like molecule; however, after sulfation, the TSPS became more branched structure than native polysaccharide. Keywords. Tamarind seed polysaccharide, conformation, light scattering.